Maternal Dietary Diversity and Growth of Children Under 24 Months of Age in Rural Dodoma, Tanzania. Issue 2 (June 2018) - Huang, Megan; Sudfeld, Christopher; Ismail, Abbas; Vuai, Said; Ntwenya, Julius; Mwanyika-Sando, Mary; Fawzi, Wafaie
Objective: To identify predictors of maternal dietary diversity in rural Dodoma, Tanzania and assess its association with child growth outcomes. Methods: A cross-sectional survey of 361 mothers with children under 24 months of age was conducted in 5 villages in rural Dodoma, Tanzania. Maternal diets were assessed using food frequency questionnaires, and dietary diversity was categorized using Minimum Dietary Diversity for Women (MDD-W) guidelines. Child anthropometric measures were taken to calculate height-for-age z -score (HAZ), weight-for-height z -score (WHZ), and weight-for-age z -score (WAZ). Linear and logistic regressions were used to examine the association between maternal dietary diversity and children's growth outcomes. Results: About 40% of mothers did not consume a diverse diet (MDD-W < 5), and 35% of children were stunted. Household production of greater number of crops was associated with greater MDD-W scores ( P < .01). Greater maternal dietary diversity was associated with significantly greater child WHZ (mean difference = 0.44; 95% confidence interval [CI]: 0.10-0.78; P = .01), WAZ (mean difference = 0.37; 95% CI: 0.08-0.65; P = .01), and reduced risk of wasting (odds ratio = 0.22; 95% CI: 0.07-0.66; P = .01). Conclusions: Greater maternal dietary diversity was associated with improved child WHZ and WAZ outcomes. Sustainable interventions to increase maternal dietary diversity may improve WHZ and WAZ in young children in similar settings.